INDONESIAN TEACHERS KNOWLEDGE AND EXPERIENCE TEACHING STUDENTS WITH DYSLEXIA - Khofidotur Rofiah; Blerta Krasniqi; Ima Kurrotun Ainin (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2026)
The study aimed to examine how Indonesian teachers’ knowledge of dyslexia and the experiences teaching students with dyslexia in the Indonesian context. 137 teachers working with students with dyslexia in regular schools participated in this study. Mixed-methods research designs combining closed and open-ended research questionnaires were employed. Data was analyzed using statistical descriptive, differences, and correlation analysis for closed-ended questions and thematic analysis was used for open-ended questions. The results revealed that the average scores of teachers’ knowledge on dyslexia was 32.99 from 50.00. The difference analysis showed that teaching experiences and ages had significant differences on teachers' knowledge of dyslexia. The correlation analysis showed that teachers’ misconceptions about dyslexia were significantly interrelated, particularly the belief that dyslexia is associated with memory deficits and below-average intelligence, which was positively correlated, while more accurate understandings of dyslexia as a language processing difficulty were negatively associated with these misconceptions. Thematic analysis to describe teachers' experiences including students with dyslexia in their classroom revealed two main themes (misunderstanding dyslexia and teaching dyslexia) and six sub themes (1) illiterate children, (2) teachers’ concerns, (3) good teachers, (4) fun methods, (5) collaboration, and (6) environment. The study suggested the importance of providing proper information, teachers’ training and seminars on understanding dyslexia as well as knowledge and practices teaching students with learning difficulties, especially students with dyslexia.